Complications After Surgical Treatment Of Anomalous Pulmonary Venous Connection (Eurasian Medical Research Periodical, 2026)
Anomalous pulmonary venous connection (APVC) is a congenital heart defect in which one or more pulmonary veins drain into the right atrium or systemic veins instead of the left atrium. This results in oxygenated blood returning to the right heart chambers, where it mixes with deoxygenated venous blood. Without timely surgical intervention, APVC leads to chronic hypoxia and progressive heart failure, affecting the child’s development and survival. Despite successful surgical correction, certain complications may arise in the postoperative period, requiring prompt attention. Literature analysis indicates that studying the outcomes and complications of APVC correction remains a highly relevant clinical issue. The aim of this study was to conduct a comparative evaluation of surgical outcomes for APVC correction depending on the type of defect and to identify the causes of mortality in the early postoperative period